Damoctocog Alfa Pegol, a PEGylated B-domain Deleted Recombinant Extended Half-life Factor VIII for the Treatment of Hemophilia A: A Product Review - Mark T. Reding; Shadan Lalezari; Gili Kenet; Giovanni Di Minno; Jonathan Ducore; Alexander Solms; Anita Shah; Pål André Holme; Lone H. Poulsen; Karina Meijer; Mindy Simpson; Maria Elisa Mancuso (Drugs in R&D)
Abstract Damoctocog alfa pegol (BAY 94-9027, Jivi®), is a site-specifically PEGylated, extended half-life recombinant factor VIII (FVIII) that is approved in several European and non-European countries for on-demand treatment and prophylaxis of bleeding in previously treated patients aged ≥﻿ 12 years with hemophilia A. Reliable measurements can be obtained using most one-stage and chromogenic FVIII assays over a wide concentration range. The efficacy, safety and pharmacokinetics (PK) of damoctocog alfa pegol have been studied extensively in the PROTECT VIII clinical trials, and its long-term safety and effectiveness profile is continuing to build through observational and interventional real-world studies. The PK of damoctocog alfa pegol was shown to be improved as compared with that of sucrose-formulated rFVIII (rFVIII-FS, Kogenate®), and was also demonstrated to be non-inferior to and, for some variables, more favorable than rFVIII-Fc fusion protein, efmoroctocog alfa (Elocta®; NCT03364998), rurioctocog alfa pegol (BAX 855, Adynovate®/Adynovi®; NCT04015492), and antihemophilic factor (recombinant) plasma/albumin-free method (rAHF-PFM, Advate®; NCT02483208). Damoctocog alfa pegol was generally well tolerated and none of the patients in any of the clinical trials, including the PROTECT VIII clinical program, HEM-POWR, or ongoing single-center studies, developed FVIII inhibitors. Efficacy for perioperative hemostasis has been demonstrated. Low bleeding rates were achieved across the studies, with twice weekly, every 5-day and every 7-day prophylaxis offering patients ≥ 12 years and their clinicians the chance to tailor treatment to individual needs and lifestyles, while maintaining long-term protection from bleeds and their consequences. Graphical Abstract